The metabolite p-cresol impairs dendritic development, synaptogenesis, and synapse function in hippocampal neurons: Implications for autism spectrum disorder - Guzman-Salas, Sheyla; Weber, Andre; Malci, Ayse; Lin, Xiao; Herrera-Molina, Rodrigo; Cerpa, Waldo; Dorador, Cristina; Signorelli, Janetti; Zamorano, Pedro (My University, 2022)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopment disorder resulting from different etiological factors, both genetic and/or environmental. These factors can lead to abnormal neuronal development on dendrite and synaptic function at the central nervous system. Recent studies have shown that a subset of ASD patients display increased circulation levels of the tyrosine metabolite, p-cresol, related to chronic intestinal disorders because of dysbiosis of the intestinal microbiota. In particular, abnormal presence of intestinal Clostridium sp. has been linked to high levels of p-cresol in ASD children younger than 8 years. However, the role of p-cresol during development of the central nervous system is unknown. Here, we evaluated in vitro the effect of p-cresol on neurite outgrowth in N2a and PC12 cell lines and dendritic morphology, synaptic density, neuronal activity, and calcium responses in primary rat hippocampal neurons. p-cresol inhibits neural differentiation and neurites outgrowth in N2a and PC12 neuronal cell lines. In hippocampal neuronal cultures, Sholl's analysis shows a decrease in the dendritic arborization of neurons treated with p-cresol. Synaptic density analyzed with the synaptic markers Piccolo and Shank2 is diminished in hippocampal neurons treated with p-cresol. Electrically evoked intracellular calcium rise was drastically, but reversely, blocked by p-cresol, whereas that spontaneous neuronal activity was severely affected by early addition of the metabolite. These findings show that p-cresol alters dendrite development, synaptogenesis, and synapse function of neurons in culture, therefore, neuronal alterations occurring in ASD children may be related to this metabolite and dysbiosis of the intestinal microbiota.
Keywords: autism; bacterial metabolite; dendrite outgrowth; p-cresol; synapses